Development of Website-Based Dile (DisasterLearn) Media for Eleventh-Grade English Subject at SMK Nusantara - Nur Azizah Agustiana; Hidayatur Rohmah; Chusnul Chotimah (Lembaga Yasin AlSys, 2026)
The integration of website-based media into English language learning offers opportunities to improve instructional accessibility, interactivity, and student engagement; however, context-specific digital resources for teaching analytical exposition texts in vocational secondary schools remain limited. This study aims to develop DiLe (DisasterLearn), a website-based learning medium for Grade XI English instruction at SMK Nusantara Bogem Diwek Jombang, and to examine students’ responses to its use. The study employed a Research and Development approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The product was validated by a media expert and a subject-matter expert before being tested with students as end users. Expert validation was conducted to assess the validity and instructional suitability of the developed medium, while students’ responses were collected through a questionnaire. The findings show that the media expert evaluation yielded an average score of 92%, categorized as highly valid, while the subject-matter expert evaluation likewise placed the product in the highly valid category. Student-response data also indicated a highly positive evaluation, as reflected in the predominance of “agree” and “strongly agree” responses across the assessed dimensions. These findings demonstrate that DiLe is highly valid and suitable for supporting the teaching of analytical exposition texts. The study contributes a contextually relevant website-based instructional resource and indicates that its implementation has the potential to strengthen students’ interest and motivation in English language learning.